Does attending an English private school benefit mental health and life satisfaction? From adolescence to adulthood. Issue 5 (3rd September 2022) - Henderson, Morag; Anders, Jake; Green, Francis; Henseke, Golo
ABSTRACT: Previous research has shown that there is a small but significant cumulative private school advantage in terms of educational attainment in Britain. However, research on how school type influences non-educational outcomes is more scarcer. This paper aims to identify the extent to which school type influences satisfaction with life and mental health from adolescence to early adulthood. Using Next Steps, a longitudinal study of young people in England born in 1989/90, the authors use multiple variable regression analyses to address the research questions. They find that for this cohort there is no evidence of a difference for mental health and life satisfaction by school type for either men or women in adolescence or early adulthood.